Rescued by the Colton cowboy - Mello, Deborah Fletcher (Coltons of Grave Gulch., 2021)
"Fiercely loyal, Soledad de la Vega would do anything to help her loved ones. So when her best friend, Annie, is murdered, Soledad vows to keep little Lyra safe--by running from a killer...and hiding out in Palmer Colton's barn. The cowboy has never really wanted a wife and kids of his own. Something about Soledad and Lyra, though, tugs at Palmer's heart like never before. Will he be able to keep his heart intact--even as he keeps them safe from a deadly threat?"--